The importance of developing handwriting skills of Grade 1 learners in the classroom - Nyamuswa, Mpho (My University, 2026)
Handwriting during the Foundation Phase is essential for the development of brain networks that facilitate superior reading skills. The ability to write by hand is a fundamental skill that teachers must instil in learners in their early grades. The Curriculum and Assessment Policy Statement for Home Language in the Foundation Phase, Grades R-3, recommends implementing a pre-handwriting programme prior to the formal instruction of handwriting. However, the curriculum does not mandate a particular pre-handwriting programme. The main aim of this study was to explore the importances of developing handwriting skills of Grade 1 learners in the classroom. This study aimed to investigate the significance of cultivating handwriting skills among Grade 1 learners in the classroom. The research utilsed Vygotsky's Socio-cultural theory. The research employed a qualitative methodology. Data was gathered by face-to-face interviews, classroom observations, and document analysis to comprehend the significance of developing learners' handwriting skills. The study population consisted of all teachers instructing Grade 1 in the Foundation Phase. Purposive sampling was employed to select six teachers instructing Grade 1 learners, as handwriting is introduced at this level. The participants in this study were chosen from three primary schools in Vhembe District, as these schools possessed more than two Grade 1 classrooms. Thematic analysis was employed to examine the data gathered from each participant. The findings speculated that teachers frequently underscore the significance of fine motor abilities in handwriting development. The anticipated conclusion of the findings is that certain learners lack the requisite fine motor control essential for accurate letter creation. The recommendation posits that teachers provide learners with increased handwriting exercises to improve their penmanship abilities.
M. Ed. in Early Childhood Education
Department of Early Childhood Education
Keywords: Cognitive development; UCTD; Fine motor skills; Handwriting development; Handwriting; Letter formation; Teaching strategies